A perspective on terra incognita: uncovering the neuroanatomy of the human subcortex - Alkemade, Anneke; Keuken, Max C.; Forstmann, Birte U. (Frontiers in Neuroanatomy, 2013)
Recent exciting advancements in the field of in-vivo neuroimaging allow for visualization of the living human brain with unprecedented anatomical detail. Large consortium studies will provide us with novel insights in the function and connectivity of the human brain. However, it is unlikely that the spatial resolution obtained using in-vivo imaging will, in the near future, approximate the level of detail obtained in post-mortem anatomical studies. Initiatives such as the recently published Big Brain project (Amunts et al., 2013) herald a novel approach in post-mortem brain research. We feel that linking data from histological observations with in-vivo imaging studies will greatly advance our understanding of the functional neuroanatomy of the human brain.